PENGEMBANGAN BAHAN AJAR FISIKA KELAS VIII SMP N 1 MEMPAWAH HILIR BERBASIS KEARIFAN LOKAL PADA MATERI GAYA - Sari Julisma (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
This researcher is a development research (R&D). The purpose of this study was to develop physicsteaching materials for class VIII based on local wisdom on style material and to determine the feasibility of theseteaching materials. The design in this study uses the 4-D or Four-D development model which stands for define,design, development, and disseminate. However, in this study the 4-D model was modified to 3-D without going through the final stage, namely deployment. It aims to develop valid media contained in the third step, namely development. The data collection technique used was an indirect communication technique and the data collectiontool was in the form of material expert and media expert validation sheets. There are also validators, namelyvalidators according to 2 material experts and 2 media experts. The instrument used is an assessment scale todetermine the quality of teaching materials using a Likert scale with five categories arranged in the form of achecklist. sBased on the results of data analysis, it can be seen that physics teaching materials for class VIII arebased on local wisdom based on assessment according to material experts with an average score of 79% withappropriate criteria, while assessment according to material experts with an average score of 77% with feasiblecriteria.